163k views
0 votes
Solve 7+7a=7(2-b) for b

2 Answers

2 votes

Answer:

b = 1 - a

Explanation:

Given

7 + 7a = 7(2 - b) ← divide both sides by 7

1 + a = 2 - b ( subtract 2 from both sides )

- 1 + a = - b ( multiply through by - 1 )

1 - a = b

User Franiis
by
5.1k points
3 votes

Answer:


b = (a - 1)

Explanation:

Question


7 + 7a = 7(2 - b)

First Solve the brackets


7 + 7a = 7(2 - b) \\ 7 + 7a = 14 - 7b

Then Make the b as the Subject


7 + 7a = 14 - 7b \\7 + 7a - 14 = 7b \\ 7a - 7 = 7b \\ 7(a - 1) = 7b \\ (7(a - 1))/(7) = (7b)/(7) \\ a - 1 = b

hope this helps you.

Have a nice day!

User Martin Geisler
by
4.4k points